ASEAN's expanding role as an FDI rule-maker - Mark Feldman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
This Perspective argues that the ASEAN-led RCEP agreement and the ASEAN Outlook on the Indo-Pacific have created significant momentum for ASEAN to further reinforce its central role in advancing Asia-Pacific economic integration.
Keywords: 330